Implementation of Active Learning Strategies at MLR Institute of Technology, Hyderabad - A Best Practice - Chugh, K. L.; Ram Mohan Rao, P. (Journal of Engineering Education Transformations, 2018)
Teacher Centred learning has been the traditional method of teaching. In this method of teaching, the Learning tends to be passive and the learners play little part in the learning process. The information flow is one-way with insufficient interaction with students in the Class Room. To overcome a number of shortcomings observed in the Teacher –Centred Learning, the focus of instruction needs to be shifted from Teacher –Centred Learning to Student-Centred Learning. There are a number of approaches to implement Student-Centred Learning in the curriculum. We have chosen Active Learning Strategies as an Instructional approach to implement Student-Centred Learning at MLR Institute of Technology-Hyderabad. As a first step, we have selected the five Active Learning Strategies to implement:1) Flipped Class Room 2) Think-Aloud- Pair-Problem-Solving (TAPPS) 3) In-Class Teams 4) Group writing Assignments and 5) Collaborative Learning. Ten IUCEE-IIEECP certified faculty have been designated as mentors to monitor the implementation process for the smooth and effective conduct of Active Learning Strategies. The Active Learning Reports are compiled in the specified template by the faculty after completion of the activity every month. The reports are evaluated by the mentors to assess their compliance vis-a-vis the requirements stipulated in the SOPs. Based on the outcome of assessments, the faculty are provided the guidance/training to overcome the observed deficiencies. The faculty in the college have started the implementation of Active Learning Strategies w.e.f July 2017. The students have responded positively to this Active Learning Pedagogy.